Administration for rural development - Mehta, D.R.(ed.); Batra,Satish K.(ed.) (Jaipur, 1981)
Since the mid-seventies, the Centre for Administrative Change has been publishing monographs and books bearing on important conceptual and empirical aspects of public administrative systems. The present volume is fourth in the series of such publications. The thematic focus of the book assumes substantial significance in view of the sprawling area of rural development activities and a renewed interest in the problems of their management.
Keywords: Rural Development